The relationship of body mass index to penile length and testicular volume in adolescent boys - Rizky Adriansyah; Muhammad Ali; Hakimi Hakimi; Melda Deliana; Siska Mayasari Lubis (Paediatrica Indonesiana, 2012)
Background Evidence suggests that obesity may be related toearly onset of puberty in girls. However, few studies have found alink between body mass index (BMI) and puberty onset in boys.More study is needed to assess the relationship of BMI to penilelength and testicular volume.Objective To investigate the relationship ofBMI to penile lengthand testicular volume in adolescent boys.Methods A crossô€€¿sectional study was carried out on adolescentboys aged 9 to 14 years in Secanggang District, Langkat Regency,North Sumatera Province in August 2009. Subjects' BMIs werecalculated by dividing body weight (BW) in kilograms by bodyheight (BH) in meters squared. Penile length (em) was measuredwith a spatula. We took the average of three measurements fromthe symphysis pubis to the tip of the glans penis. Testicular volume(mL) was estimated by palpation using an orchidometer. Pearson'scorrelation test (r) was used to assess the relationship of BMI topenile length and BMI to testicular volume.Resu lts There were 108 participants, consisting of 64primary school students and 44 junior high school students.Subjects' mean age was 11.7 (SO 1.62) years; mean BWwas 35.2 (SO 8.48) kg; mean BH was 1.4 (SO 0.11) m;mean BMI was 17.5 (SO 2.34) kg/m'; mean penile lengthwas 4.5 (SO 1.25) cm; and mean testicular volume was 3.6(SD 1.20) mL. We found no significant association betweenBMI and penile length (rô€€»-0.25, Pô€€»0.06), nor betweenBMI and testicular volume (rô€€»-O.21; Pô€€»O.09).Conclusion T here was no significant relationship ofBMI to penilelength nor BMI to testicular volume in adolescent boys.[Paediatr lndanes. 2012;52:267-71].